ABC Dependent Cancer Suppression - PRASANNA. P; SHANMUGANATHAN .S; MATHITHUMILAN.B; KARTHIKEYAN. S (International Journal of Pharma and Bio Sciences, 2011)
ATP-binding cassette transporters (ABC-transporter) are members of a protein super family that is one of the largest and most ancient families with representatives in all extant phyla from prokaryotes to humans.ABC transporters are transmembrane proteins that utilize the energy of adenosine triphosphate (ATP) hydrolysis to carry out certain biological processes including translocation of various substrates across membranes and non-transport-related processes such as translation of RNA and DNA repair. They transport a wide variety of substrates across extra- and intracellular membranes, including metabolic products, lipids and sterols, and drugs. They are classified as ABC transporters based on the sequence and organization of their ATP-binding cassette (ABC) domain(s). ABC transporters are involved in tumor resistance, cystic fibrosis, bacterial multidrug resistance, and a range of other inherited human diseases. Human ABC transporters are involved in several diseases that arise from polymorphisms in ABC genes and rarely due to complete loss of function of single ABC proteins. These proteins are characterized by the presence of two nucleotide-binding domains, and present recent study aims at the association and dissociation of these domains is a common basic molecular mechanism of operation that couples ATP binding/hydrolysis to substrate transport across membranes. Using biosoftware tools, the structural prediction for transmembrane glycoproteins targeted cancer cells were also studied.